MAYORITAS KERAMIK YUAN DI TROWULAN: KONTRA REALITA HUBUNGAN MAJAPAHIT Â€“ CINA PADA ABAD KE 13-15 MASEHI - Kusmartono, Vida Pervaya Rusianti (Berkala Arkeologi, 2002)
The Majapahit Empire and its relationship with China demonstrated the implementation of policies that did not always work harmoniously. This is inseparable from the background conditions of each kingdom. Political instability, both at home and abroad, was marked by misunderstandings, rebellions or wars and the severance of bilateral relations between Majapahit and China. However, archaeological data show an interesting phenomenon that political factors do not have a significant impact on socio-economic aspects. Yuan ceramics that were found in abundance at the Trowulan Site - especially in the Nglinguk, Sentonorejo, and Pendopo Agung Sectors - prove that exchange or trading activities continue to be effective. The continuation of this activity is thought to have occurred due to the use of two methods of exchange / trade, namely legal and illegal, which were carried out by traders who often stopped by in Majapahit.